Mediasi Determinan Integritas Laporan Keuangan Dengan Manajemen Laba - Patmawati, Patmawati; Sari, Relasari; Rahmawati, Meita (Owner : Riset dan Jurnal Akuntansi, 2024)
This study examines the determinants of financial statement integrity using variables of institutional ownership, managerial ownership, independent commissioners, leverage, company size, and audit committee mediated by profit management variables. The population used in this study is all state-owned companies listed on the Indonesia Stock Exchange with sampling techniques using purposive sampling methods based on certain criteria. Testing the research data using a panel regression model using the GEE Population-Averaged Model approach. The purpose of this study is to examine the direct influence using variables of institutional ownership, managerial ownership, independent commissioners, leverage, company size, and audit committee as well as indirect influence on financial statement integrity variables through profit management. The results of this study show that there is no influence of institutional ownership variables, independent commissioners, leverage, company size, and audit committee on financial statement integrity, there is an influence of managerial ownership on financial statement integrity, and profit management is proven as mediation on financial statement integrity only for managerial ownership variables.